Biotechnology of Lactulose Production: Progress, Challenges, and Prospects - Svetlana A. Ryabtseva; Andrey G. Khramtsov; Maria A. Shpak; Alexey D. Lodygin; Georgy S. Anisimov; Serafima N. Sazanova; Yulia A. Tabakova (Техника и технология пищевых производств)
Lactulose is a prebiotic that has found a wide application in medicine and food industry. Commercial lactulose is usually synthesized by isomerization in alkaline media at high temperatures. Enzymatic methods offer a more sustainable alternative and require more moderate processing conditions. This review covers 44 years of scientific publications (1978–2022) on the enzymatic synthesis and purification of lactulose. The materials were retrieved from Scopus, Web of Science, PubMed, and Elibrary databases. The enzymatic approach to lactose-to-lactulose conversion has two methods: isomerization (direct) and transgalactosylation (via hydrolysis). Isomerization exploits cellulose-2-epimerases, but their safety status is still rather vague. As a result, cellulose-2-epimerases are not commercial. Epilactose is a by-product of isomerization. Transgalactosylation involves β-galactosidases with an official international safety status (GRAS). It is available on the market, and its action mechanism is well understood. This article systematizes various data on the conditions for obtaining the maximal yields of lactulose by different enzymes. The Kluyveromyces lactis yeast and the Aspergillus oryzae mold are the main sources of β-galactosidases in lactulose production. The yield can reach 30% if the processing conditions are optimal. Fructose remains the main problem in the production process. No scientific publications revealed a direct relationship between the maximal yields of lactulose and the molar fructose-tolactose ratios. Cellobiose epimerases make it possible to achieve high yields of lactulose (70–80%). However, these enzymes are associated with genetic engineering and mutagenesis, which challenges their safety status. The most promising trends in lactulose biotechnology include secondary dairy raw materials, immobilized enzymes, membrane reactors, complex production processes, lactose-to-lactulose conversion, and purification of final product.